ELLIPSIS PHENOMENON IN SENTENCES FOUND IN NOVEL SHERLOCK HOLMES - Maharani, Putu Devi (Sphota : Jurnal Linguistik dan Sastra, 2019)
Ellipsis is one of phenomenon in language use. Traditionally, ellipsis is the grammar means that avoids repetitions, abandons the old information, highlights key words and make the context connected tightly. The structure of the sentence that occur ellipsis phenomenon of course will have changed and quite different with the common grammatical sentence which used the rules but still have same meaning. There is lot of ellipsis phenomenon happened in discourse, one of them is in written text such a novel. In novel we can find various phenomenon of language use by the author to make the story leave a certain impression, interesting and not boring in reading it. Novel Sherlock Holmes was chosen as the data source of this research because there are a lot of type ellipsis phenomenon found. It mainly aimed at investigating types of ellipsis phenomenon occurred in the novel completed by showing the structure of constituent that construct the sentences in tree diagram. The discussion is not only in Syntax view point, this research also tries to describe the function of the ellipsis, because actually ellipsis  is not only used for the speaker’s economy but it can have many other function such can remove ambiguity, can convey non-expressible aspect of meaning, can establish discourse coherence and contribute to a positive rapport with the hearer (Hendriks & Spenader: 2005). Knowing how the ellipsis happened can be an important thing to identify the functions. The data focused on the sentences that got from narration and dialogs that found in this fictional private detective novel. The method of collecting the data used direct observation method by reading the novel which contains 1059 pages, then collected the sentences which occur ellipsis, checked the structure of the sentences while choosing some sentences that represent various sentence structure of elliptical phenomenon and functions based on theory used. After the data collected, they analyzed by some theories. The types of ellipsis phenomenon analyzed using Kiss and Alexiadou (2015) collected theories, then the structure investigated by Brown (1991) theory, and the function analyzed by Hendricks & Spenader (2005) theory.